Enhancing the Acyltransferase Activity of Candida antarctica Lipase A by Rational Design. Issue 12 (14th July 2015) - Müller, Janett; Sowa, Miriam A.; Fredrich, Birte; Brundiek, Henrike; Bornscheuer, Uwe T.
Abstract A few lipases, such as Candida antarctica lipase A (CAL‐A), are known to possess acyltransferase activity. This enables the enzyme to synthesize fatty acid esters from natural oils and alcohols even in the presence of bulk water. Unfortunately, fatty acids are still formed in these reactions as undesired side‐products. To reduce the amount of fatty acids, several CAL‐A variants were rationally designed based on its crystal structure. These variants were expressed in Escherichia coli and Pichia pastoris, purified, and their acyltransferase/hydrolase activities were investigated by various biocatalytic approaches. Among the investigated variants, mutant Asp122Leu showed a significant decrease in the hydrolytic activity, thus reducing the side‐product yield during acylation. As desired, this variant retained wild‐type process‐relevant features like pH profile and thermostability.